(untitled) (Bangladesh Journal of Public Administration, 2021)
In line with the global goals for sustainable development (SDG goals), UNWTO has emphasized sustainable tourism development for achieving SDGs targets in the member countries. Bangladesh has already identified tourism as a thrust sector for the development of the country. The present study identifies the opportunities and contributions of tourism activities for achieving SDGs in Bangladesh. This study analyses the existing tourism policies and plans, government regulations, reports, and SDG related practices to attain the objectives. It is observed that SDG goals number 8, 12, and 14 are directly related to tourism. Furthermore, tourism can contribute to achieving some other SDG goals, like 3, 11, and 15. The study reveals that the contributions of tourism to GDP and employment are in an increasing trend. Sustainable Consumption and Production practices are encouraging the tourism businesses to include nature and biodiversity conservation in their management plans. Marine tourism development in the Bay-of-Bengal can play a positive role in reducing the negative impact of climate change and sustainable use of the oceans, seas, and marine resources. The study reveals that sustainable tourism development through cultural, religious, and archeological features can make Dhaka a stable and sustainable city. The study shows that sustainable tourism development in protected areas can ensure the preservation of forest areas, protect biodiversity conservation and provide sustainable use of natural resources. Sustainable tourism development can ensure long-term social, economic, and environmental benefits to all stakeholders to contribute a sustainable development in Bangladesh.